Comparison of Four Gastrotomy Closure Techniques in Dogs - Abdelkader, Rasha E.; Ahmed, Ahmed F.; Abd-elghaffar, Sary Kh.; Semieka, Mohamed (Journal of Advanced Veterinary Research, 2023)
This study aimed to evaluate and compare four double-layer closure techniques for canine gastrotomy. Twenty adult clinically healthy mongrel dogs of both sexes were involved in the present study. Dogs were randomly allocated into four groups; A, B, C, and D (n=5 for each group) based on the used technique for gastrotomy closure. In group A, the first layer of the stomach wall (mucosa and submucosa) and the second layer (tunica muscularis and tunica serosa) were closed in simple continuous suture pattern. In group B, both layers were closed using inverting suture pattern. In group C, the first layer was closed by inverting suture pattern, while the second layer was closed by simple continuous suture pattern. In the group D, the first layer was closed by simple continuous suture pattern, while the second layer was closed by stabling using the skin staplers. Physiological parameters (rectal temperature, heart rate, and respiratory rate) and the body weight were taken preoperatively, 7 and 14 days post-operatively. Dogs were euthanatized 14 days, postoperatively. The four techniques were evaluated for the procedure time, closure efficiency, postoperative complications, and histopathology.